Helminth Infection of Children in Ngemplak Seneng Village Klaten - Fitri Nadifah; Desto Arisandi; Nurlaili Farida Muhajir (Journal of Health (JoH), 2016)
Helminth infection remains one of health problems of Indonesian people for years. The tropical condition of Indonesian climates with high level humidity has believed to be the one of factors that increase the number of this infection cases. Based of many studies, the number of helminth infections is related to the poor of hygiene and sanitation. This study is conducted to know the percentages of helminth infections among 0-14 years old children in Dusun Ngemplak, Desa Ngemplak Seneng, Klaten and also their personal hygiene with questionaire instruments. To know helminth infection in subjects, we examine faeces sample with simple method and 1% eosin dye. As the results of examination, we found Trichuris trichiura egg in three samples. This might related to the poor of their hygienic behaviors. Some of the behavior such as wash hand before eating and after defecation, use sandal or shoes when playing, consume helminthic drug for last 6 months, and defecate in toilet has shown percentage under 70%. Other behaviors such as cutting and cleaning nails and use a spoon when eating has shown percentage above 70%.